2003
DOI: 10.1046/j.1442-2026.2003.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient mortality as related to triage category in three New South Wales regional base hospitals

Abstract: Objective: To establish the incidence of death after admission via the ED for each of the five categories of the Australasian Triage Scale in three New South Wales base hospitals, and to compare this with published data from an adult tertiary referral hospital in Victoria. To examine the causes of death in each category. Methods: Information was collected from databases established as part of quality assurance projects at three New South Wales rural base hospitals from 1 January 2000 to 31 December 2000. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…‐ 21 One approach is based only on less urgent triage categories, 21 but this has been discredited because patients in these categories often require longer consultation time, more imaging and pathology tests, and have a much higher admission rate than patients seen in general practice 2 . They also have a substantial mortality rate after admission to the hospital 22 . Other studies have identified common features of GP‐type visits, including being self‐referred, not arriving by ambulance, being assigned triage category 4 or 5, and being subsequently discharged from the ED 2 , 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…‐ 21 One approach is based only on less urgent triage categories, 21 but this has been discredited because patients in these categories often require longer consultation time, more imaging and pathology tests, and have a much higher admission rate than patients seen in general practice 2 . They also have a substantial mortality rate after admission to the hospital 22 . Other studies have identified common features of GP‐type visits, including being self‐referred, not arriving by ambulance, being assigned triage category 4 or 5, and being subsequently discharged from the ED 2 , 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the urgency of each presentation to an ED is rated by a triage nurse using the five‐level Australasian Triage Scale (ATS). Nationally and internationally, the increase in less urgent (ATS 4 and 5) presentations has prompted some to argue that less urgent problems such as minor injuries, which do not require specialist attention, could be better managed in primary health‐care settings 14–16 . Conversely, others have argued that even these less urgent presentations could not easily be managed in a conventional general practice setting, and that their attendance at ED is not only appropriate, but medically necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ATS 4 and 5 patients as a group experience substantially higher levels of morbidity and mortality than patients in primary health‐care settings 17,18 . Furthermore, there is some preliminary evidence that at least in Australia, these less urgent patients might be characterized by significant social, psychiatric and substance‐related problems 16 . If it is indeed the case that the prevalence of substance use and mental health problems is higher among less urgent, apparently more disadvantaged patients, this would have important implications for service provision not only within an ED setting, but across the whole spectrum of health‐care services.…”
Section: Introductionmentioning
confidence: 99%
“…One of these relates to the relationship (or not) between triage classification and ‘primary care’ status, with the common confusion between urgency and severity or complexity. For example, we know that Australian Triage Scale (ATS) category 4 and 5 patients have combined admission rate to hospital of >20% 1 while general practice patients overall have an admission rate of <1% 2 . Of patients subsequently admitted, high death rates (up to 2.6%) occur in ATS category 4 patients 3 .…”
Section: ‘Primary Care’ and Emergency Department Casemixmentioning
confidence: 92%